2018
DOI: 10.3389/fphys.2018.00595
|View full text |Cite
|
Sign up to set email alerts
|

Training Characteristics During Pregnancy and Postpartum in the World’s Most Successful Cross Country Skier

Abstract: This case-study investigated the training characteristics, physiological capacity, and body composition of the world’s most successful cross country skier during the 40-week pregnancy, and the 61-week postpartum. Training data was systemized by training form (endurance, strength, and speed), intensity [low- (LIT), moderate- (MIT), and high-intensity training (HIT)], and mode (running, cycling, and skiing/roller skiing). The training volume [mean ± standard deviation (median)] during pregnancy was 12.9 ± 7.3(10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 25 publications
3
58
0
Order By: Relevance
“…Indicatively, L 4 decreased after a long period of reduced training volume and intensity, despite a greater dilution of blood lactate in the 4% higher BV, but quickly improved with increased volume and intensity. This is in line with a previous study ( Solli and Sandbakk, 2018 ), where VO 2 at the estimated lactate threshold rapidly increased up to- (wk 6–12), and above (wk 13–20) pre-pregnancy values during the postpartum period in a successful Olympic athlete. Overall, this case study suggests some lingering hematological benefits and underlines the positive effect of a quick resumption of LIT with a gradually increasing intensity of training in the first 12 weeks after delivery.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Indicatively, L 4 decreased after a long period of reduced training volume and intensity, despite a greater dilution of blood lactate in the 4% higher BV, but quickly improved with increased volume and intensity. This is in line with a previous study ( Solli and Sandbakk, 2018 ), where VO 2 at the estimated lactate threshold rapidly increased up to- (wk 6–12), and above (wk 13–20) pre-pregnancy values during the postpartum period in a successful Olympic athlete. Overall, this case study suggests some lingering hematological benefits and underlines the positive effect of a quick resumption of LIT with a gradually increasing intensity of training in the first 12 weeks after delivery.…”
Section: Discussionsupporting
confidence: 93%
“…While the previously estimated risk of premature birth and low birth-weight following high volumes of endurance training during pregnancy, has been rejected ( Haakstad and Bo, 2011 ; Thangaratinam et al, 2012 ; Di Mascio et al, 2016 ), findings indicate an increased abortion risk with very high training volumes and/or HIT during the first weeks after conception ( Hegaard et al, 2016 ). In this context, the total training volume performed during pregnancy in the current case is clearly lower than in a previous study ( Solli and Sandbakk, 2018 ) but showed the same relative reductions in training volume throughout pregnancy as previous studies ( Potteiger et al, 1993 ; Bailey et al, 1998 ; Solli and Sandbakk, 2018 ; Sundgot-Borgen et al, 2019 ). In contrast to these studies, our participant also conducted relatively large amounts of HIT during the first trimester.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…She trained during pregnancy, gave birth to a healthy baby, won four medals in the subsequent World Championship and became the most successful competitor of all time in the winter Olympics in February 2018. Unfortunately, she experienced two sacral stress fractures during postpartum 11…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a meta-analysis focusing on health outcomes after pregnancy in elite athletes found very low certainty evidence of no association between pre-pregnancy elite athletic exposure and initiation of breastfeeding postpartum, nor the length of breastfeeding postpartum [ 19 ]. Importantly breastfeeding has been shown to have a deleterious effect on bone mineral density (BMD) due to the loss of calcium from the maternal bone mass [ 73 , 74 ], which may increase the risk of bone stress injury [ 37 , 75 , 76 ]. Whilst the link between breastfeeding and injury is weak, with no evidence of this association among elite athletes, breastfeeding athletes should take precautions to increase impact load gradually, with appropriate muscle strengthening to support a return to impact activities.…”
Section: Postnatal Implicationsmentioning
confidence: 99%